Clinical effectiveness of nimodipine for the prevention of poor outcome after aneurysmal subarachnoid hemorrhage: A systematic review and meta-analysis - Hao, Guangzhi; Chu, Guangxin; Pan, Pengyu; Han, Yuwei; Ai, Yunzheng; Shi, Zuolin; Liang, Guobiao (Frontiers in Neurology, 2022)
Abstract: Objective: In clinical practice, nimodipine is used to control cerebral vasospasm (CVS) which is one of the major causes of severe disability and mortality in patients with aneurysmal subarachnoid hemorrhage (aSAH). However, the exact efficacy of nimodipine-use for patients with aSAH are still controversial due to the lack of sufficient and up-to-date evidence. Methods: In this meta-analysis, the latest databases of the Cochrane Central Register of Controlled Trials, PubMed-Medline, Web of Science, Embase, Scopus, and OVID-Medline were comprehensively searched for retrieving all randomized controlled trials (RCTs) regarding the efficacy of nimodipine in aSAH patients. The primary outcome was poor outcome, and the secondary outcomes were mortality and cerebral vasospasm (CVS). After detailed statistical analysis of different outcome variables, further evidence quality evaluation and recommendation grade assessment were carried out. Results: 13 RCTs met the inclusion criteria and a total of 1727 patients were included. Meta-analysis showed that poor outcome was significantly reduced in nimodipine group (RR, 0.69 [0.60–0.78]; I2=29%). Moreover, nimodipine also dramatically decreased the mortality(RR, 0.50[0.32-0.78]; I2=62%) and the incidence of CVS (RR, 0.68[0.46-0.99]; I2=57%). Remarkably, we found poor outcome and mortality were both significantly lower among aSAH patients with the mean age＜50 than that mean age≥50 by subgroup analysis. Further, the evidence grading of poor outcome and its age subgroup in this study was assessed as high. Conclusion: Nimodipine could significantly reduce the incidence of poor outcome, mortality and CVS in aSAH patients. Moreover, we strongly recommended that aSAH patients, especially those younger than 50 years old, should use nimodipine as early as possible in order to achieve a better clinical outcome, whether oral medication or endovascular direct medication.